2016
DOI: 10.1097/mou.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Medical and surgical management of neurogenic bowel

Abstract: Many medical and surgical options are available for patients with NBoD. Selecting the appropriate medical or surgical treatment involves a careful evaluation of each patient's physical, psychosocial, financial, and geographic variables in an effort to optimize bowel function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 75 publications
0
11
0
6
Order By: Relevance
“…Individuals with SCI frequently experience neurogenic bowel dysfunction, which may be characterized by stool retention, constipation, and fecal incontinence [3]. In addition to adversely affecting patient quality-of-life [4,5] and being an enormous burden on the healthcare system [6], neurogenic bowel dysfunction can lead to a host of life-threatening sequelae such as intestinal obstruction, recurrent urinary tract infections from chronic constipation, and hemorrhoidal disease [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with SCI frequently experience neurogenic bowel dysfunction, which may be characterized by stool retention, constipation, and fecal incontinence [3]. In addition to adversely affecting patient quality-of-life [4,5] and being an enormous burden on the healthcare system [6], neurogenic bowel dysfunction can lead to a host of life-threatening sequelae such as intestinal obstruction, recurrent urinary tract infections from chronic constipation, and hemorrhoidal disease [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To limit the harmful effects of these potentially disastrous consequences, clinicians have developed several management modalities for SCI patients with bowel dysfunction, ranging from conservative (targeting diet and bowel habits) to invasive (e.g. sacral anterior root stimulation and permanent colostomy) [8,9]. Despite these strategies, there is no definitive cure for neurogenic bowel dysfunction, making it a chronic, life-altering condition.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, this goal has often only been achieved by resorting to surgical procedures such as the Malone ACE, or even ostomy. Such traditional surgical continence procedures can indeed be highly effective in carefully selected patient groups [155], but they carry a relatively high risk of surgical complications and an increased risk of anesthesiology procedures. The advent of TAI changed traditional bowel management for the significant numbers who do not respond to conservative and pharmacological approaches alone, permitting successful treatment of a large population of pediatric and adolescent patients with NBD, without requiring surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach for NBD in children primarily involves creating artificial "upstream" access for antegrade administration of colonic irrigation enemas, either by Malone's antegrade continence enema (ACE) procedure, or by tube cecostomy. This might be especially advantageous in patients with stool impaction due to NBD [155] or in those who, due to comorbidities, lack the balance, manual dexterity, or motivation to self-administer retrograde washouts by TAI [13]. Many teenagers can administer their antegrade enemas independently via an intermittently inserted catheter or an indwelling tube.…”
Section: Bowel Surgerymentioning
confidence: 99%
“…The antegrade colonic enema (ACE), originally described by Malone et al, 1 has been shown to be effective in the management of fecal incontinence and chronic constipation in children with neurogenic bowel dysfunction where oral medical treatment and retrograde irrigation have failed. 2 In the case of a missing or atrophic appendix, alternative methods must be considered. In our institution, ileal neoappendicostomy (INA) has become the method of choice using the terminal ileum, preserving the ileocecal valve as an antireflux mechanism.…”
Section: Introductionmentioning
confidence: 99%